Comparing the reliability of software systems: A case study on mobile operating systems - Ivanov, Vladimir; Reznik, Alexey; Succi, Giancarlo (Information sciences, 2018)
Assessment of software reliability is inevitable in modern software production process. Many works aimed at better models for measurement and prediction of reliability of software products. Tens of approaches have been developed and evaluated so far. However, very few works focus on approaches to compare existing systems with respect to reliability. Despite a tremendous importance to practice (and software management area), a complete and sound comparison methodology does not exist. In this paper, we propose a methodology for software reliability comparison. The methodology extensively applies the GQM approach and software reliability growth models. The methodology has been thoroughly evaluated on a case of assessment and comparison of three open source mobile operating systems: Sailfish, Tizen and CyanogenMod.